“A novel that does not uncover a hitherto unknown segment of existence is immoral”. A Conversation with Marek Bieńczyk on Milan Kundera’s Works (Conducted by Olga Żyminkowska) - Bieńczyk, Marek; Żyminkowska, Olga (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The interview with Marek Bieńczyk covers, in general, the subject of the philosophy of novel by Milan Kundera and the reception of his works nowadays in Poland and abroad. Marek Bieńczyk – the French translator of Milan Kundera’s novels – talks about the history of his first translations and the beginnings of scientific thinking about Kundera. Moreover, he explains the problems connected with Kundera’s authorial and elaborate philosophy of novel: the conception of narrator, hero and composition. Bieńczyk also narrates his own memories with M. Kundera. What is more, he indicates the inspirations he draws in his own work from innovative prose by Czech novelist, who is celebrating his 91st anniversary this year.